Fungicides Films of Low-Density Polyethylene (Ldpe)/Inclusion Complexes (Carvacrol and Cinnamaldehyde) Against Botrytis Cinerea - Rabagliati-Canessa, F; Yanez-Sanchez, M; Ortiz-Nunez, J; Zapata-Ramirez, P; Canales-Arévalo, D; Cament-Riveros, A (Multidisciplinary Digital Publishing Institute (MDPI), 2019)
Low density polyethylene (LDPE) films were prepared with the incorporation of natural agents (carvacrol and trans-cinnamaldehyde) by the melting process. The co-precipitation method was used successfully to complex the carvacrol or trans-cinnamaldehyde with β-cyclodextrin (β-CD). The active compounds encapsulated in β-CD achieved ca. 90% encapsulation efficiency (E.E.). The inclusion complex studied by scanning electron microscopy (SEM) found particles of different sizes, ca. 4 μm. The active compounds were added directly (1 and 5 wt %) into the polymer matrix, yielding LDPE + carvacrol and LDPE + cinnamaldehyde films. The active compounds encapsulated in β-cyclodextrin (β-CD) were added to LDPE, yielding LDPE + β-CD-carvacrol and LDPE + β-CD-cinnamaldehyde films. The incorporation of carvacrol and trans-cinnamaldehyde, and their corresponding inclusion complexes with β-cyclodextrin, did not affect the thermal properties of LDPE. The microcapsules distributed in all polymer matrices had sizes of 5-20 μm as shown by scanning electron microscopy (SEM). In terms of mechanical properties, the polymers showed a slight decrease of Young s modulus (12%) and yield stress compared (14%) to neat LDPE. This could be due to the essential oil acting as a plasticizer in the polymer matrix. The LDPE + carvacrol and LDPE + cinnamaldehyde films had the capacity to inhibit fungi by 99% compared to neat LDPE. The effectiveness against fungi of LDPE+β-CD + active agent was slower than by the direct incorporation of the essential oil in the LDPE in the same amount of active agent. The biocidal properties were related to the gradual release of active compound from the polymer. The results confirm the applicability of carvacrol, trans-cinnamaldehyde, and their corresponding inclusion complexes in active packaging, as well as their use in the food delivery industry. © 2019 by the authors.